1991
DOI: 10.1002/cjoc.19910090310
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photochromism of 3‐indylfulgides

Abstract: Six fulgides of indole series are prepared. Three of them are photochromic. The others in which R1 is hydrogen atom do not show photochromism. Only Z‐E isomerizations occur on irradiation at 365 nm. The effects of molecular structural modifications on photochromic properties are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Previously reported indolylfulgides substituted at the 3-position on the indole and having hydrogen at the bridging position were initially obtained in their E -form and also could not be converted to the C -form 23-25. For the first time, we obtained the C -form of such a fulgimide with a hydrogen at the bridging position.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Previously reported indolylfulgides substituted at the 3-position on the indole and having hydrogen at the bridging position were initially obtained in their E -form and also could not be converted to the C -form 23-25. For the first time, we obtained the C -form of such a fulgimide with a hydrogen at the bridging position.…”
Section: Resultsmentioning
confidence: 91%
“…Photochromic studies demonstrated that 6C can be converted to 6E ( E -form due to IUPAC priority rules), but the reverse reaction was not observed (Scheme ). Previously reported indolylfulgides substituted at the 3-position on the indole and having hydrogen at the bridging position were initially obtained in their E -form and also could not be converted to the C -form. For the first time, we obtained the C -form of such a fulgimide with a hydrogen at the bridging position. We did not investigate the optical properties of 6 further as it was not photochromic.…”
Section: Resultsmentioning
confidence: 92%
“…At this juncture, the wavelength of these transitions can be compared to that of an experimentally reported spirofused polycyclic aromatic compounds are found to exhibit UV-absorption in 332-335 nm range. [40] Other transitions involving canonical orbitals and the contribution of each transition towards the excited state in percentage have been included in Table 4. M1 and M2 show a difference in the range of n to π* and π to π* UV-visible transitions.…”
Section: Charge Transfer After Excitationmentioning
confidence: 99%
“…The stretching vibrations of B-H bonds have the same characteristics of multiply peaks at 2600-2700 cm -1 with high intensity as para isomers. 17,18,27…”
Section: Ir Spectramentioning
confidence: 99%
“…This computational method has ever been used to optimize the structures of 10 and 11 vertexes closo-heteroboranes and the optimized geometries are in good agreement with the experimental parameters. [15][16][17][18] It was also successfully applied to compute 12 vertexes closo-heteroboranes and their halogeno derivatives. As shown in Table 1, the bond parameters of three molecules, 1-SB 11 H 11 , 1-SeB 11 H 11 , and 12-Cl-1-SB 11 H 10 , are consistent with those obtained from experimental structures.…”
mentioning
confidence: 99%